Mampukah Sulawesi Selatan Mendukung Ketahanan Pangan di Kawasan Timur Indonesia? - Alfi, Kamal Maulana; Budiasih, Budiasih; Rohmah, Apriliani Nur; Azizah, Shinta Marwah; Rahmi, Meautia; Nafiis, Faried Akbar (Seminar Nasional Official Statistics, 2023)
Food is one of the essential factors for human life. Generally, the Eastern Indonesia Region (KTI) is a vulnerable area in terms of food security. However, in 2019, South Sulawesi Province had the highest rice production in the Eastern Indonesia Region (KTI). This has implications for the government's determination to make South Sulawesi the center for food security in the Eastern Indonesia region. Therefore, this research presents strong evidence supporting South Sulawesi as the center for food security in the Eastern Indonesia region. The method used is multiple linear regression to demonstrate the influence of rice production and per capita expenditure share on food on the level of food security. The results of this research support the government's decision to designate South Sulawesi Province as the center for food security in the Eastern Indonesia Region.